STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYAT SI BAGEJE DI JORONG SAWAH MUDIK NAGARI BATAHAN KECAMATAN RANAH BATAHAN KABUPATEN PASAMAN BARAT - Oktalina, Lidia; Abdurahman, Abdurahman; Hamidin, Hamidin (Universitas Negeri Padang, 2013)
The article aims to describe the structure and function of social folklore si Bageje in Jorong Sawah Mudik Nagari Batahan Subdistrickof Ranah Batahan West Pasaman Regency.The data were analyzed by using the following procedures: (1) the stage of data description, (2) translate the data into Indonesian (3) the stage of data classification/analysis, (4) the stage of the discussion and conclusions of the results of the classification or data analysis, and (5) reporting stage. It can be concluded that the structure of the folklore si Bageje that all ocated in Jorong Sawah Mudik Nagari Batahan Subdistrick of Ranah Batahan West Pasaman Regencyâ€ consists of grove/plot, character, setting, theme and mandate. Moreover, the social function of folklore in Jorong Sawah Mudik Nagari Batahan Subdistrick of Ranah Batahan West Pasaman Regency, are: (1) educational function, (2) the bequeath function, (3) the identity function, and (4) the function of tradition.